PENINGKATAN KINERJA SUMBER DAYA MANUSIA MELALUI MODAL SOSIAL, KEGIATAN BERBAGI PENGETAHUAN, DAN INOVASI - Herni Wati (Jurnal Riset Bisnis Indonesia, 2013)
This research aims to examine and analyze; (1) the impact of social capital towards knowledgesharing activities, (2) the impact of social capital and knowledge sharing toward innovation, and (3)the impact of social capital, knowledge sharing, and innovation toward human resource performance.This study used 57 employees from the administration staffs of IAIN Walisongo Semarang as sample.The findings shows that (1) social capital has a positive impact on knowledge sharing and innovation,(2) social capital and knowledge sharing have no positive impact on human resource performance,(3) social capital and knowledge sharing may have a positive impact on human resource performanceonly through innovation, (4) innovation has a positive impact on human resource performance.Keywords: Social Capital, Knowledge Sharing Activities, Innovation, Human Resource Performance.